A cultura da inovação e as tecnologias das indústria 4.0 em concreteiras - Dal Pizzol, Mauro Andreolla (My University, 2022)
It is a fact that organizations aim to stand out in the market and obtain advantages that differentiate them from their competitors. For this to be possible, it is important to know yourself and your competitor, and choose between the different strategies which are applicable to each context. Seeking this knowledge, this master's research focuses on analyzing the culture of innovation and the technologies of Industry 4.0 in concrete companies, delimiting the study to organizations that are part of the Brazilian Association of Concrete Services Companies - ABESC. With a qualitative and exploratory approach, the research is based on two research categories: on the culture of innovation in organizations, and on the set of enabling technologies of Industry 4.0. These two research categories were coded into five themes: innovation, innovative environments, culture, innovative attitudes and Industry 4.0 technologies. Data were collected through open structured interviews applied with representatives of the concrete segment and later analyzed using the NVivo software. The research results indicate that in the culture of innovation category the subcategories that stand out are: values and beliefs, cultural aspects, influences and new methods and new products. In the Industry 4.0 category, the following stood out: information management, lack of knowledge, horizontal and vertical system integration, cyber security and big data and data analysis. [resumo fornecido pelo autor]
É fato que as organizações almejam se destacar no mercado de atuação e obter vantagens que a diferencie de seus concorrentes. Para que isso seja possível, é importante conhecer a si mesmo e ao seu concorrente, e escolher entre as diferentes estratégias quais são aplicáveis a cada contexto. Buscando este conhecimento, essa pesquisa de mestrado tem como foco analisar a cultura da inovação e as tecnologias da Indústria 4.0 em concreteiras, delimitando o estudo a organizações que fazem parte da Associação Brasileira das Empresas de Serviços de Concretagem - ABESC. Com uma abordagem qualitativa e exploratória a pesquisa está embasada em duas categorias de pesquisa: na cultura da inovação em organizações, e no conjunto das tecnologias habilitadoras da Indústria 4.0. Estas duas categorias de pesquisa foram codificadas em cinco temáticas: inovação, ambientes inovadores, cultura, atitudes inovadoras e tecnologias da Indústria 4.0. Os dados foram coletados por meio de entrevistas estruturadas abertas aplicadas junto aos representantes do segmento do concreto e posteriomente analisados através do software NVivo. Os resultados da pesquisa indicam que na categoria cultura da inovação as subcategorias que se sobressaem são: valores e crenças, aspectos culturais, influências e novos métodos e novos produtos. Na categoria Indústria 4.0 se destacaram: gerenciamento das informações, falta de conhecimento, integração horizontal e vertical do sistema, segurança cibernética e big data e análise de dados. [resumo fornecido pelo autor]
Keywords: Automação industrial; Inovações tecnológicas; Indústria 4.0; Industrial automation; Industrial automation; Technological innovations; Industry 4.0